Параметры биохимической устойчивости торфов - Inisheva, L. I.; Maslov, S. G.; Dementjeva, T. V.; Szajdak, L. W.; Инишева, Л. И.; Маслов, С. Г.; Дементьева, Т. В.; Шайдак, Л. (Издательство Тюменского государственного университета, 2015)
The 140 representative samples of peat were selected on the territory of the taiga zone of Western Siberia to work out the criteria of biochemical stability of peats. The basic technical characteristics and the composition of organic matters of peats were studied. The systematic approach was used to reveal the factors of biochemical stability of peats. The study of the fractional makeup of nitrogen confirmed the leading role of the botanical composition of peats in the distribution of nitrogen compounds according to fractions. Raised bog peats have proved to be less nitrogen-enriched than low-mire peats, particularly the peats of the moss group. The peats of the moss group are characterized by the lowest content of total nitrogen and the low content of easy hydrolysable factions as well as by the increased content of poorly-hydrolysable and non-hydrolysable fractions. The revealed differences of the fractional makeup of nitrogen in peats with a different botanical composition are correlated with the differences of the factious-group composition of organic matters. The correlation analysis has shown that the most significant parameters (out of the 38 parameters taken) are (i) the sum of humic acids,(ii) the content of carbohydrates (hydrolysable and poorly-hydrolysable), (iii) the non-hydrolysable remainder, (iv)the C/N ratio (carbon-to-nitrogen ratio), (v) the sum of hydrolysable and mineral nitrogen and (vi) the content of lipides. These parameters may serve as possible parameters of the biochemical stability of peats. На территории таежной зоны Западной Сибири были отобраны 140 представительных для Западной Сибири образцов торфов с целью разработки критериев биохимической устойчивости торфов. В торфах были изучены общетехнические свойства, состав органического вещества. Для выявления показателей биохимической устойчивости торфов использовали системный метод. Исследование фракционного состава азота подтвердило ведущую роль ботанического состава торфов в распределении соединений азота по фракциям. Верховые виды торфа значительно меньше обогащены азотом, чем низинные, особенномоховой группы, которая характеризуется самым низким содержанием общегоазота, низкой долей легкогидролизуемых фракций и повышенной – трудногидролизуемых и негидролизуемых фракций.Выявленные различия фракционного состава азота в торфах разного ботанического состава в общих чертах согласуются с различиями фракционно-группового состава органического вещества. Корреляционный анализ показал, что наиболее значимыми параметрами (из взятых 38 параметров) являются: сумма гуминовых кислот, содержание углеводов (легко- и трудногидролизуемых), негидролизуемого остатка, отношение C/N, сумма легкогидролизуемого и минерального азота и содержание липидов. Это дает основание считать их наиболее важными и рассматривать как возможные параметры биохимической устойчивости торфов.